Moving from trends to benchmarks by using regression tree analysis to find inbreeding thresholds in a critically endangered bird. Issue 4 (21st January 2021) - Flanagan, Alison M.; Masuda, Bryce; Grueber, Catherine E.; Sutton, Jolene T.
Abstract: Understanding how inbreeding affects endangered species in conservation breeding programs is essential for their recovery. The Hawaiian Crow ('Alalā) ( Corvus hawaiiensis ) is one of the world's most endangered birds. It went extinct in the wild in 2002, and, until recent release efforts starting in 2016, nearly all of the population remained under human care for conservation breeding. Using pedigree inbreeding coefficients ( F ), we evaluated the effects of inbreeding on Hawaiian Crow offspring survival and reproductive success. We used regression tree analysis to identify the level of inbreeding (i.e., inbreeding threshold) that explains a substantial decrease in 'Alalā offspring survival to recruitment. Similar to a previous study of inbreeding in 'Alalā, we found that inbreeding had a negative impact on offspring survival but that parental (vs. artificial) egg incubation improved offspring survival to recruitment. Furthermore, we found that inbreeding did not substantially affect offspring reproductive success, based on the assumption that offspring that survive to adulthood breed with distantly related mates. Our novel application of regression tree analysis showed that offspring with inbreeding levels exceeding F = 0.098 were 69% less likely to survive to recruitment than more outbred offspring, providing a specific threshold value for ongoing population management. Our results emphasize the importance of assessing inbreeding depression across all life history stages, confirm the importance of prioritizing parental over artificial egg incubation in avian conservation breeding programs, and demonstrate the utility of regression tree analysis as a tool for identifying inbreeding thresholds, if present, in any pedigree‐managed population. Abstract : Article impact statement : Regression tree analysis is a useful tool for identifying inbreeding thresholds for genetic management of populations in human care. Abstract : Moverse de las Tendencias a los Referentes Mediante el Análisis de Árbol de Regresión para Encontrar los Umbrales de Endogamia de una Ave en Peligro Crítico Resumen: Es necesario entender cómo afecta la endogamia a las especies en peligro que se encuentran en programas de reproducción para la conservación para la recuperación exitosa de estas especies. El cuervo hawaiano ('Alalā) ( Corvus hawaiiensis ) es una de las especies de ave que se encuentra en mayor peligro de extinción en todo el mundo. Esta especie se extinguió en vida libre en el 2002 y no fue hasta los recientes esfuerzos de liberación que iniciaron en 2016 que casi toda la población permaneció bajo cuidado humano en programas de reproducción para la conservación. Usamos los coeficientes de linaje endogámico ( F ) para evaluar los efectos de la endogamia sobre el éxito reproductivo y de supervivencia de la descendencia de los cuervos hawaianos. Usamos un análisis de árbol de regresión para identificar el nivel de endogamia (es decir, el umbral de endogamia) que explicara una disminución sustancial en la supervivencia de la descendencia de 'Alalā hasta el reclutamiento. Similar a un estudio previo de la endogamia en los 'Alalā, descubrimos que la endogamia tuvo un impacto negativo sobre la supervivencia de la descendencia pero que la incubación parental (vs. la artificial) de huevos mejoró la supervivencia de la descendencia hasta el reclutamiento. Además, encontramos que la endogamia no afectó de manera importante al éxito reproductivo de la descendencia, esto basado en la suposición de que los descendientes que sobreviven hasta la edad adulta se reproducen con parejas cuya relación familiar es lejana. Nuestra aplicación novedosa del análisis de árbol de regresión mostró que la descendencia con niveles de endogamia que exceden F = 0.098 tuvieron 69% menos de probabilidad de sobrevivir hasta el reclutamiento que aquella progenie con menor endogamia, lo que proporciona un valor específico de umbral para el manejo continuo de la población. Nuestros resultados resaltan la importancia de la evaluación de la depresión endogámica en todas las etapas de la historia de vida, confirman la importancia de priorizar la incubación parental de huevos sobre la artificial en los programas de conservación de aves y demuestran la utilidad del análisis de árbol de regresión como herramienta para identificar los umbrales de endogamia, cuando presentes, en cualquier población manejada por linaje.